From Logs to Rankings: A Quantitative Framework for SEO Performance Diagnosis Using Server Data and Search Console Signals - Ananya Sharma Ananya Sharma; Ravi Kumar Singh Ravi Kumar Singh (Kalam Practica Media, 2025)
This article presents a quantitative framework for SEO performance diagnosis that integrates server log analysis, Google Search Console signals, and on-site telemetry to measure three controllable components of organic visibility: crawl efficiency, indexability, and ranking stability. The framework introduces operational metrics including crawl-to-index yield, waste rate by URL class, discovery latency for new pages, canonical consistency, and volatility indices for query clusters, and it proposes an engineering workflow that maps observed organic underperformance to testable hypotheses and prioritized interventions. A generic, non-site-specific case design is used to demonstrate how the framework distinguishes between growth constraints caused by crawl budget fragmentation, indexation suppression due to duplication and canonical conflicts, and ranking instability associated with performance regressions and thin semantic coverage. Results illustrate that log-derived crawl patterns frequently diverge from sitemap expectations and that large fractions of crawler activity can be consumed by low-value parameterized URLs, which reduces effective discovery of high-value pages, while Search Console data can reveal impression ceilings and click-through inefficiencies that remain invisible in traffic-only dashboards. The paper contributes applied guidance for practitioners by translating SEO into measurable system components, providing reproducible diagnostic steps, and emphasizing governance through monitoring and controlled experimentation rather than ad hoc optimization, thereby aligning SEO practice with engineering reliability principles suitable for OJS-based applied technology publication.